Posterior cranial fossa meningiomas: Comparison of results between patients older and younger than 70 years - Luciano Mastronardi; Alberto Campione; Amer Ahmad Alomari (Brain and Spine)
Introduction: Surgical strategy for meningioma resection in the elderly is controversial: diverse studies in the literature have pointed at the age as a negative prognostic factor in terms of postoperative results. Research question: The aim of this study is to compare surgical outcomes after resection of posterior fossa meningiomas in <70 and ≥ 70 years-old age groups. Material and methods: We reviewed 72 patients affected by posterior fossa meningiomas who underwent surgical treatment at San Filippo Neri Hospital, Rome, Italy between September 2010 and December 2022. We analyzed data regarding tumor size, clinical presentation, extent of resection and complication/mortality. Results: The groups consisted of 52 (72,2%) young and 20 (27,8%) elderly patients. Gross total resection rate was significantly higher among youngsters (p = 0,013), mainly for planned subtotal removal in older patients. At 3-month follow-up, clinical improvement was seen in 19 (36,5%) young and 7 (35,0%) elderly patients, which raised at last follow-up, being 84,6% (44) and 80,0% (16), respectively (p = 0,406). Two cases of progression/recurrence among the elderly and 1 among youngsters were observed; one case of mortality among the elderly was reported. Discussion and conclusions: Safety data regarding postoperative complications and mortality in our series seem to confirm that there is no significant difference between older and younger patients, as long as older patients are carefully selected. Therefore, if surgery is proposed, it should be radical if gross total resection could be safely attempted.